2017
DOI: 10.1002/ecy.2075
|View full text |Cite
|
Sign up to set email alerts
|

Resource availability underlies the plant‐fungal diversity relationship in a grassland ecosystem

Abstract: It is commonly assumed that microbial communities are structured by "bottom-up" ecological forces, although few experimental manipulations have rigorously tested the mechanisms by which resources structure soil communities. We investigated how plant substrate availability might structure fungal communities and belowground processes along an experimental plant richness gradient in a grassland ecosystem. We hypothesized that variation in total plant-derived substrate inputs, plant functional group diversity, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 86 publications
6
80
1
Order By: Relevance
“…Rotations with annual cover crops increased fungal and AMF biomass (Maul et al, 2014), as well as the relative proportion of fungi making up the soil microbial biomass (Lehman et al, 2014), but decreased plant pathogen numbers (Benitez et al, 2016). In grasslands, a higher plant biomass was associated with increases in both fungal phylogenetic and functional group diversity (Cline et al, 2018). In our study, genera that increased with cover crops were dominated by Ascomycetes, but also included members of Zygomycota and Basidiomycota.…”
Section: Cover Cropping Effectssupporting
confidence: 46%
See 1 more Smart Citation
“…Rotations with annual cover crops increased fungal and AMF biomass (Maul et al, 2014), as well as the relative proportion of fungi making up the soil microbial biomass (Lehman et al, 2014), but decreased plant pathogen numbers (Benitez et al, 2016). In grasslands, a higher plant biomass was associated with increases in both fungal phylogenetic and functional group diversity (Cline et al, 2018). In our study, genera that increased with cover crops were dominated by Ascomycetes, but also included members of Zygomycota and Basidiomycota.…”
Section: Cover Cropping Effectssupporting
confidence: 46%
“…The diversity and duration of seasonal coverage by plants also play a role in shaping soil microbial communities due to the quantity and variety of organic substrates they provide via exudates and residues to the soil community (Cline et al, 2018;Sievers and Cook, 2018;Zhalnina et al, 2018). A meta-analysis of 122 studies concluded that microbial biomass increased by 20.7% when one or more crops were added to a monoculture, and the biomass increases correlated with increases in soil C (3.6%) and N pools (5.3%) (McDaniel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, enhanced bacterial and fungal species richness through grassland restoration may come from positive linkages between aboveground and belowground alpha diversities. Consistent with microbial taxonomic richness, plant species richness also has indispensable effects on bacterial metabolic and genetic functions as well as on fungal pathotrophs and saprotrophs due to altered resource availability via plant restoration (Cline et al, ). Aside from nutrient‐mediated linkages, increased plant richness diversifies the host range for microbes, accommodating a greater variety of plant symbiotic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Among the total fungi, the saprotrophic composition was only significantly predicted by SOC. Saprotrophic fungi generally act as the primary decomposers, so that SOC can influence their composition as the main resource; meanwhile, the relative importance of SOC could be raised up when plant influence is impeded .…”
Section: Discussionmentioning
confidence: 99%